2020
DOI: 10.1051/shsconf/20207503009
|View full text |Cite
|
Sign up to set email alerts
|

Systematicity of students’ independent work in the course of operating systems

Abstract: The paper is devoted to the study of systematicity of students’ learning activity as a parameter of student’s model, and influence of systematicity at learning results in the course “Operating Systems”. The necessity to equip the student himself as the subject of the educational process with the skills and appropriate pedagogical forecasting tools for independent choice of the appropriate variant of educational activity is shown as theoretical framework. Parameters of models in such pedagogical diagnostics sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The use of e-learning is based on and used in the learning process of virtual environments [5,18,24], complemented by the reality of computer simulations, virtual 3D worlds with the effect of immersion. According to the numerous studies [11,12,14,19,25,35,44], the virtual environment is a quality educational tool, and the task of the teacher is to reorient modern virtual technologies to learning.…”
Section: Resultsmentioning
confidence: 99%
“…The use of e-learning is based on and used in the learning process of virtual environments [5,18,24], complemented by the reality of computer simulations, virtual 3D worlds with the effect of immersion. According to the numerous studies [11,12,14,19,25,35,44], the virtual environment is a quality educational tool, and the task of the teacher is to reorient modern virtual technologies to learning.…”
Section: Resultsmentioning
confidence: 99%
“…Scientists and teachers note that the main difficulties were unclear requirements, lack of special literature, and inconsistency of tasks with the subject of the course. The results of a survey of students on the use of information technologies in performing individual tasks showed that they mainly used lecture notes and electronic resources, rather than textbooks or other educational materials when preparing for classes [18]. They faced such problems as lack of material in books, lack of time, problems with finding information, too much information, which makes it difficult to study.…”
Section: Information Searchmentioning
confidence: 99%
“…Another advantage of the e-course is the opportunity to receive fast feedback, possibility of visual presentation of educational material and critical reflective learning and most importantly -motivation increase [26]. In this way Moodle LMS and the implementation of the idea of advanced professional education will not only significantly increase the possibility of a person's self-determination in the world of professional labour, but also help a person to adapt to the conditions of a dynamically changing maritime industry [27,28]. And by increasing the general and professional literacy of future maritime transport specialists in constantly changing environment, it will contribute to the effective development of production and the economy as a whole.…”
Section: Organization Of Networking Cooperation At Kherson State Marimentioning
confidence: 99%